TRACKING OF LOW-SIZED TARGETS FROM NON-STATIONARY CAMERA BASED ON COVARIANCE FEATURES AND PREDICTOR - I. A. Baryskievic; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A fast selective-covariance tracking method of low-sized targets from non-stationary camera is proposed. It is based on selective predictor and representation of spatial and statistical target properties by covariance matrix. The comparison of proposed selective-covariance and known covariance methods is provided.